2017
DOI: 10.1088/1361-648x/aa75c2
|View full text |Cite
|
Sign up to set email alerts
|

Packing in protein cores

Abstract: Proteins are biological polymers that underlie all cellular functions. The first high-resolution protein structures were determined by x-ray crystallography in the 1960s. Since then, there has been continued interest in understanding and predicting protein structure and stability. It is well-established that a large contribution to protein stability originates from the sequestration from solvent of hydrophobic residues in the protein core. How are such hydrophobic residues arranged in the core; how can one bes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 87 publications
(194 reference statements)
1
26
0
Order By: Relevance
“…Figure A clearly shows that the distributions P(ϕ) of packing fractions of core residues in the Dun1.0, PPI, and TM datasets are all very similar with mean values, ϕ=0.56±0.02, 0.56 ±0.02, and 0.55 ±0.01, respectively. In prior studies, we showed that this packing fraction matches the value for random close packing of elongated, bumpy particles that match the aspect ratio and surface roughness of core amino acids …”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Figure A clearly shows that the distributions P(ϕ) of packing fractions of core residues in the Dun1.0, PPI, and TM datasets are all very similar with mean values, ϕ=0.56±0.02, 0.56 ±0.02, and 0.55 ±0.01, respectively. In prior studies, we showed that this packing fraction matches the value for random close packing of elongated, bumpy particles that match the aspect ratio and surface roughness of core amino acids …”
Section: Resultssupporting
confidence: 62%
“…In this study, we investigate whether the same approach can predict the conformations of amino acid side‐chains at protein‐protein interfaces and in transmembrane proteins. The reason the hard‐sphere model can accurately predict side‐chain conformations in protein cores is because they are densely packed . We therefore first calculated the packing fraction of the cores of protein‐protein interfaces and transmembrane proteins, and compared these values with the packing fraction of the cores of soluble proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of packing fraction ϕ of core residues in proteins whose structures are determined by X-ray crystallography occur over a relatively narrow range, with a mean of 0.55 and an SD of 0.02. 46,48,51 We define core residues as those with small values of the relative solvent accessible surface area, rSASA ≤ 10 −3 (see Section 4 for a description of the database of high-resolution protein X-ray crystal structures and definition of rSASA). In contrast, we find that many of the CASP submissions and 3DRobot decoys possess core residues with packing fractions that are much higher than those in experimentally determined proteins structures.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] Additionally, in our previous work, we have found that several features of core packing are universal among well-folded experimental structures, such as the repacking predictability of core residue side chain placement, core packing fraction, and distribution of core void space. [46][47][48][49][50][51] This work suggests that analysis of core residue placement and packing in proteins more generally should be effective in determining the accuracy of protein decoys. Indeed, software to assess X-ray crystal structure model quality often calculates interatomic overlaps, 53,54 the RosettaHoles software uses defects in interior void space to differentiate between high-resolution X-ray crystal structures and protein decoys, 52 VoroMQA scores protein decoys using a statistical potential based on Voronoi contact areas, 34 and many other decoy detection methods attempt to incorporate predictions of solvent accessibility.…”
Section: Introductionmentioning
confidence: 96%